Evaluation of the effect of curing techniques on colour property of acrylic resins - Nadira A Hatim; Amer A Taqa; Radhwan H Hasan (University of Mosul, College of Dentistry, 2004)
This study was carried out to evaluate the colour property of two types of acrylic resin materials cured by microwave tech-nique in comparison with that cured by conventional water bath technique. Two types of heat cured acrylic resin materials were selected: Quayle-Dental and Major-base types. Seventy-two sam-ples (30×20×1.5 mm) were prepared and divided into four experimental groups: Quayle-Dental and Major-base groups were cured by microwave technique and the others Quayle-Dental and Major-base groups were cured by water-bath techni-que. The number of samples for each gr-oup was 18. The colour property for the samples was evaluated using computerized ultra-violet-visible spectrophotometer with acc-uracy up to 0.001 nm. The absorbed light was measured which is also termed the optical density. The results of this study showed that there were no significant differences in optical density for acrylic resin samples cured by microwave and water-bath tech-niques, and the acrylic resin with smaller particle size (Quayle-Dental) showed hi-gher optical density (colour property) than that of larger particle size (Major-base).